Worker flows and reallocation in COVID-19 exposed sectors in the Danish economy - Filip Rozsypal (Danmarks Nationalbank, 2020)
Past worker flows show that among the sectors hit hard by the COVID-19 epidemic, workers in "Transportation" accumulate relatively more human capital. In the event of large worker reallocation, this sector's productivity would be hit harder and need longer to recover due to the loss of firm and sector-specific knowledge and skills of the departing workers.
Keywords: 330; Coronavirus; Arbeitsmobilität; Humankapital; Verkehrssektor; Freizeitwirtschaft; Gastgewerbe; Dänemark